Empirical Evaluation of Transit Signal Priority: Fusion of Heterogeneous Transit and Traffic Signal Data and Novel Performance Measures. Issue 1 (January 2015) - Feng, Wei; Figliozzi, Miguel; Bertini, Robert L.
Transit signal priority (TSP) can reduce transit delay at signalized intersections by making phasing adjustments. TSP is a relatively inexpensive and easily implemented tool to make transit service faster and more reliable. TSP also sends a signal that a city or region encourages the growth of transit. With the aim of assessing the performance of an existing TSP system, this study had access to a unique set of high-resolution bus and traffic signal data. Novel algorithms and performance measures were proposed. The results indicate that a timely and effective TSP system requires a high degree of sophistication, monitoring, and maintenance. Empirical data suggested that most TSP phase adjustments were granted within the cycle in which buses requested priority but that only a small proportion resulted in reduced delay. In this study, many green extension phases were granted late and were therefore less effective than early signal phases. Despite this situation, the TSP system did not increase delays for passengers and vehicles when side street traffic was considered.